Mewujudkan Kesadaran Hukum Melalui Pembentukan Kelompok Sadar Hukum Di Desa Banjarsari Kabupaten Blitar - Nurdiansah, Muhamad Andre (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2024)
Most of the legal problems arise from the lowest layers of the population, including the village of Banjarsari in Blitar district. These problems often arise from a lack of public awareness and knowledge of the law. Then, from that, the government, through Kemenkumham, created a program of village-building/law-consciousness to address the problem. The implementation of community service activities is to help realize the program. The method used in this service is a directed discussion that begins with the legal approval of legal aid. The result of this service activity is the formation of the Banjarsari Village Legal Awareness Group. The enthusiasm of the participants and the Banjarsari Village Government is high enough for this dedication program, as it can help solve legal problems that may arise in the village.